2002
DOI: 10.1021/jf0206163
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Activities of Oolong Tea

Abstract: While the antioxidative properties of green and black tea have been extensively studied, less attention has been given to these properties in oolong tea. The reducing powers, the 2,2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activities, the amount of total phenolic compounds, the inhibitory effect on FeCl(2)/H(2)O(2) (Fenton reaction system)-induced DNA damage, and the inhibitory effect on erythrocyte hemolysis of an oolong tea water extract (OTE) were evaluated in the present study. The OTE was found to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
176
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(198 citation statements)
references
References 46 publications
10
176
0
3
Order By: Relevance
“…Many studies have shown that the antioxidant activities of the natural products are closely related to their biofunctionalities. [33,34] Potent antioxidant property of MECM, revealed in the present investigation may therefore be important in the future research works to study the underlying mechanism of its various medicinal properties. Further research can also explore the particular antioxidant principle(s) from the C. maxima aerial parts extract which can be one of the potent lead compound(s) from the arsenal of natural products.…”
Section: Resultsmentioning
confidence: 78%
“…Many studies have shown that the antioxidant activities of the natural products are closely related to their biofunctionalities. [33,34] Potent antioxidant property of MECM, revealed in the present investigation may therefore be important in the future research works to study the underlying mechanism of its various medicinal properties. Further research can also explore the particular antioxidant principle(s) from the C. maxima aerial parts extract which can be one of the potent lead compound(s) from the arsenal of natural products.…”
Section: Resultsmentioning
confidence: 78%
“…As seen in Figure 7, silymarin is an effective ABTS zþ radical scavenger in a concentration-dependent manner (10 -20 mg/mL, r 2 :0.9488). EC 50 The inhibition of superoxide radical generation by silymarin is higher than for a-tocopherol and trolox but lower than BHA and BHT. As seen in Figure 5, the inhibition of superoxide anion radical generation by 30 mg/mL concentration of silymarin was found to be 40.2%.…”
Section: Resultsmentioning
confidence: 92%
“…It was reported in many studies that the activities of natural antioxidants were closely related to their biofunctionalities. The reduction of chronic diseases, DNA damage, mutagenesis, carcinogenesis and inhibition of pathogenic bacterial growth is often associated with the termination of free radical propagation in biological systems [50]. Antioxidant capacity is widely used as a parameter for medicinal bioactive components.…”
Section: Discussionmentioning
confidence: 99%
“…The 1 max , used for the absorbance measurements are 515 nm (Gomez-Alonso et al 2003;Lebeau et al 2000), 516 nm (Schwarz et al 2001), 517 nm (Lu and Foo 2000;Zhu et al 2002), 518 nm (Leitao et al 2002) and 520 nm (Kim et al 2002). A reaction time of 30 min was followed by Kim et al (2002).…”
Section: Recommended Methods Of Measurement and Interpretationmentioning
confidence: 99%